PENERAPAN MARKETING MIX DALAM STRATEGI REKRUITMEN SISWA BARU SEKOLAH BERBASIS PESANTREN - Suciptono (Sekolah Tinggi Islam Kendal, 2021)
Every school must always try to be exist, develop, and be able to progress for next era. So schools need to determine and implement strategies or methods, as well as carry out marketing activities. Educational services marketing activities carried out by schools can change people's assessment of school quality in the long run and are a way to build the school's image as a whole. Seeing the current phenomenon, schools at least prepare an unusual strategy for marketing educational services, one of which is by trying new techniques and business-based marketing strategy in educational institutions, namely the marketing mix. Based on the data presentation and discussion, it can be found and described the marketing strategy for Islamic boarding school-based education services in increasing customer loyalty. It was found that educational services marketing strategy planning in increasing customer loyalty was arranged in the school public relations program and school strategic plan. Next is the implementation of educational services marketing strategy in increasing customer loyalty. In its implementation, this is done by providing excellent service, good relations between schools and customers of education services as well as publication of unique school learning, namely module-based with reference to the Islamic boarding school-based curriculum.